Carolyn Stern: capstone - Stern, Carolyn, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist viewing the world, I am intrigued by places I have not explored. As a kid and even now, I am always curious about what is beyond the hill in front of me and then what is beyond that. I will look out on a view and wish to be on the next hill over so I can see what the world is like from over there. I recognize this tendency as an insatiable craving to know and to see it all. Unfamiliar landscapes carry a sense of peace and mystery that I am attracted to and interested in encapsulating. Even though I know humans have traversed over virtually the entire world and no landscape remains unobstructed from humanity's influence, there is still a sense of intrigue surrounding a landscape that appears seemingly free of development. Naturally occurring formations and growth create a visually stimulating world that is complex, yet harmonious. These forms, as well as the feelings evoked upon experiencing nature, have inspired my current body of paintings. Within my work, the visual language used translates the landscape from realistic to the daydream world of color, brushstroke, and texture that encourages the viewer's own internal investigations of place and the desire of the unknown.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting; printmaking